2022
DOI: 10.1007/jhep02(2022)097
|View full text |Cite
|
Sign up to set email alerts
|

The joy of factorization at large N: five-dimensional indices and AdS black holes

Abstract: We discuss the large N factorization properties of five-dimensional supersymmetric partition functions for CFT with a holographic dual. We consider partition functions on manifolds of the form $$ \mathrm{\mathcal{M}}={\mathrm{\mathcal{M}}}_3\times {S}_{\upepsilon}^2 $$ ℳ = ℳ 3 × S ϵ 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 85 publications
1
9
0
Order By: Relevance
“…The result (1.2) is in complete agreement with the general holographic expectations based on gravitational blocks [13] and correctly reproduce the entropy of the rotating AdS 4 × S 7 black holes found in [5]. Similar large N factorizations hold in higher dimensions too [8]. In this paper we work to all orders but perturbatively in .…”
Section: Jhep12(2022)025supporting
confidence: 82%
See 2 more Smart Citations
“…The result (1.2) is in complete agreement with the general holographic expectations based on gravitational blocks [13] and correctly reproduce the entropy of the rotating AdS 4 × S 7 black holes found in [5]. Similar large N factorizations hold in higher dimensions too [8]. In this paper we work to all orders but perturbatively in .…”
Section: Jhep12(2022)025supporting
confidence: 82%
“…Then we can study the saddle point approximation of the refined index matrix model (2.1) with respect to u i and m i . The method has been efficiently used to study five-dimensional indices [6][7][8].…”
Section: A Direct Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main result of this section will be that the supersymmetric action (2.9), together with the associated constraint (2.10) and flux quantization conditions (2.11), localize to integrals over the fibres X ± over the poles of the spindle. 9 We refer to these contributions as gravitational blocks, since they generalize similar (conjectured) formulas that have already appeared in the literature -see [23,25,30,45,48,51,52].…”
Section: Spindly Gravitational Blocksmentioning
confidence: 70%
“…There it was shown that the entropy can be obtained by extremizing certain entropy functions that are obtained by summing ("gluing") basic building blocks. This observation was inspired by the factorization of partition functions of N = 2 field theories in d = 3, proven in [46] (for later developments in field theory see also [47][48][49]). In subsequent work [30] it was shown that for the class of explicit supergravity solutions associated with M2 and D3-branes 3 wrapping spindles, obtained by uplifting solutions in D = 4, 5 STU gauged supergravity theories on S 7 , S 5 , respectively, it is possible to write the off-shell trial entropy and trial central charge in the form of gravitational blocks, both for the twist and the anti-twist [30,31,[34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%